Five-year outcome of peripherally inserted central catheters in adults: a separated infectious and thrombotic complications analysis. (10th July 2021) - González, Samuel; Jiménez, Pedro; Saavedra, Pedro; Macías, Desiré; Loza, Ana; León, Cristóbal; López, Magdalena; Pallejá, Elena; Hernández-Socorro, Carmen Rosa; Ruiz-Santana, Sergio
Abstract: Objective: To assess infectious and thrombotic complications of peripherally inserted central catheters (PICCs) in adults. Design: A 5-year prospective cohort study. Setting: Tertiary-care teaching hospital in Seville, Spain. Patients: Adult patients undergoing PICC insertion. Methods: Catheter-associated bloodstream infection (CABSI) including catheter-related bloodstream infection (CRBSI), primary bacteremia (PB), and upper extremity deep vein thrombosis (UEDVT) were recorded. Independent predictors of complications were assessed by multivariate analysis. Results: In total, 1, 142 PICCs were inserted, with 153, 191 catheter days (median, 79). Complications included 66 cases of CABSI (5.78%; 0.43‰ catheter days), 38 cases of CRBSI (3.33%; 0.25‰ catheter days), 28 cases of PB (2.45%; 0.18‰ catheter days), and 23 cases of UEDVT (2.01%; 0.15‰ catheter days). The median times to infection were 24, 41, and 60 days for CRBSI, PB, and UEDVT, respectively. Parenteral nutrition (odds ratio [OR], 3.40; 95% confidence interval [CI], 1.77–6.52) and admission to the hematology ward (OR, 4.90; 95% CI, 2.25–10.71) were independently associated with CRBSI and PB, respectively. Admission to the hematology ward (OR, 12.46; 95% CI, 2.49–62.50) or to the oncology ward (OR, 7.89; 95% CI, 1.77–35.16) was independently associated with UEDVT. The crude mortality rate was 24.8%. Only 2 patients died of complications. Conclusions: PICCs showed a low rate of thrombotic and infectious complications. Compared to PB, CRBSI showed significantly different risk factors, a higher incidence density per catheter days, and a shorter median time to infection. Separate analyses of CRBSI and PB are more specific and clinically useful when analyzing infectious complications.